Radiation monitoring of environmental objects in zone of the influence of the research WWR-M reactor of the Institute for Nuclear Research, National Academy of Sciences of Ukraine - V. V. Tryshyn; O. V. Svarichevska; I. O. Pavlenko; N. M. Dzyatkovska; A. D. Sajenyuk; A. J. Kuzmina (Ядерна фізика та енергетика)
Results of many year investigations of environmental radiation monitoring in zone of the influence of research nuclear reactor WWR-M of the Institute for Nuclear Research of Ukrainian Academy of Science are presented. Data of radionuclide influence on low atmosphere layers of air, soil, superficial and discarded water are shown.